Transparência das sociedades de economia mista listadas em bolsa: uma perspectiva a partir dos websites - Ferraz, Hector Rodrigo Ribeiro Paes (2017)
The present study examines and evaluates public policies that promote transparency and the disclosure of data on web portals. The focus of the analysis is on state-owned enterprises listed on the Brazilian Stock Exchange (BM&FBOVESPA).These enterprises are evaluated in conformity with obligations imposed upon them by the aforementioned policies, as well as the Court of Auditors, the Ministry of Transparency, the Ministry of Planning, State Legislative Assemblies, and the national Congress. Propositions are then made for improvements in structure and organization of transparency policies, for the benefit of investors and society.